ANALYSIS OF KNOWLEDGE OF PREGNANT WOMEN ON THE CORRECT POSITION FOR THE ACTIVITIES OF DAILY LIFE (Fiep Bulletin - online, 2015)
Introduction: The gestational period is characterized as a time of transformation in women's lives, because, beyond the physical and physiological changes are also observed changes in emotional state. Thus, there are several changes that occur in the pregnant woman's body systems. Objectives: To assess the knowledge of pregnant women about proper positioning during AVD's. Method: The work it was a cross-sectional, quantitative in nature, held at the Reference Center for Social Assistance (CRAS). Pregnant women in all trimesters of pregnancy over the age of 18 years. The research was conducted through a semi-structured questionnaire with objective questions. Results: It has been confirmed, the knowledge of pregnant women about the correct placement in the realization of some postures in their activities of daily living such as: throwing, lifting, pulling and sweeping water, and not knowing about these sitting posture and grasp objects being in high places high importance at this stage, so getting clear the high levels of the same discomforts in this important phase. Conclusion: However, it is known and confirmed that pregnant women enrolled and treated at CRAS city MARIZÓPOLIS-PB, are knowledgeable of some postures like throwing, lifting, pulling and sweeping water, which is extremely important to its current state. For both unaware of crucial positions for the day-to-day like to sit down and pick up objects in high places, the data show that they were unaware of the correct way. Therefore it is of paramount importance for the guidance of the same means of lectures, workshops and primarily during their attendance at antenatal.
Keywords: Pregnancy; Postural Changes; correctpositioning.